دراسة تحليلية استشرافية لأثر العملات الرقمية المشفرة على النظام النقدي العالمي العملة الرقمية المشفرة للصين نموذجا - نورالهدى حميتي (Universty Of El-oued جامعة الوادي, 2025)
الملخص: تتناولهذهالأطروحةإحدىأكثرالقضاياتطورًافيالاقتصادالنقديالعالمي،حيثتشهدالساحةالدوليةتحولاتجذريةمعتصاعددورالعملاتالرقمية،وفيهذاالسياق،يكتسباليوانالرقميالصينيأهميةاستراتيجيةمتزايدة،ليسفقطكابتكارنقدي،بلكأداةذاتأبعادماليةوتجاريةوجيو-اقتصاديةيمكنأنتعيدرسمملامحالنظامالنقديالدولي. وسطهذاالمشهدالمتغير،تبرزتساؤلاتحاسمةحولمصيرهيمنةالدولارالأمريكيالتيامتدتلعقود،وحولقدرةالصينعلىإعادةرسمموازينالقوىالنقديةالعالميةمنخلالأداتهاالرقميةالجديدة. تهدفهذهالدراسةإلىتحليلواستشرافالأثرالمحتمللليوانالرقميعلىبنيةالنظامالنقديالعالمي،متسائلةًعماإذاكانتالعملةالرقميةالصينيةقادرةفعلاًعلىإعادةهيكلةالنظامالقائموتحديهيمنةالدولار،أمأنهامجردلاعبجديدضمنمنظومةمتعددةالأقطاب. ولمعالجةهذهالقضيةالمحورية،تمتطويرستفرضياتفرعيةتغطيالأبعادالتكنولوجية،المؤسسية،النقدية،والجيو-اقتصاديةللعملاتالرقمية. اعتمدتالدراسةمنهجًامتكاملاًيجمعبينالتحليلالنظريالمعمّق،وبناءسيناريوهاتمستقبليةمحتملة،واستخدامنماذجتنبؤيةكميةمتقدمة (LSTM،XGBoost،والانحدارالمتعدد) لتقديرسلوكثمانيةمؤشراتنقديةوماليةرئيسيةلسلةالعملاتالدولية. كشفتالنتائجعنمشهدأكثرتعقيداًمماقديبدوللوهلةالأولى: فاليوانالرقمييُحققبالفعلصعودًاتدريجيًامدعومًاببنيةتحتيةرقميةقويةورؤيةاستراتيجيةطويلةالمدى،إلاأنتأثيرهالعالميمايزالمحدودًافيالمدىالقريب. تشيرالنماذجالتنبؤيةإلىأناليوانالرقميلايشكّلفيالوقتالراهنتهديدًامباشراًوحاسماًللدولار،بليرجّحأنيكوندورهتكامليًاضمنالنظامالنقديالدولي،ممثلاًمرحلةانتقاليةحاسمةنحونظامنقديأكثرتعدديةوتوازناً. system. Amid this shifting landscape, critical questions emerge regarding the fate of U.S. dollar hegemony—which has endured for decades—and China's capacity to reconfigure the global monetary balance of power through its novel digital instrument. This study aims to analyze and forecast the potential impact of the digital yuan on the structure of the global monetary system, examining whether the Chinese digital currency is genuinely capable of restructuring the existing order and challenging dollar dominance, or whether it represents merely a new player within an increasingly multipolar framework. To address this pivotal question, six subsidiary hypotheses were developed, encompassing the technological, institutional, monetary, and geo-economic dimensions of digital currencies. The study employs an integrated methodological approach combining in-depth theoretical analysis, construction of prospective future scenarios, and deployment of advanced quantitative predictive models (LSTM, XGBoost, and Multiple Regression) to estimate the behavior of eight key monetary and financial indicators for the international currency basket. The findings reveal a landscape more complex than may initially appear: while the digital yuan is indeed achieving gradual ascendancy supported by robust digital infrastructure and long-term strategic vision, its global impact remains limited in the near term. Predictive models indicate that the digital yuan does not currently constitute a direct and decisive threat to the dollar; rather, its role is likely to be complementary within the international monetary system, representing a critical transitional phase toward a more multipolar and balanced monetary order.
أطروحة دكتوراء
Keywords: العملةالرقمية; العملةالرقميةللبنكالمركزي; اليوان الرقمي; النظام النقدي الدولي; نمذجة سيناريوهات; التنبؤ; الترميز الاقتصادي